Long term effectiveness of intravenous immunoglobulin in Churg-Strauss syndrome. Issue 12 (16th November 2004) - Danieli, M G; Cappelli, M; Malcangi, G; Logullo, F; Salvi, A; Danieli, G
Abstract : Objective: To study the long term effectiveness of intravenous immunoglobulin and plasmapheresis associated with prednisone and cyclophosphamide in Churg-Strauss syndrome. Subjects and methods: We studied 18 subjects with new onset Churg-Strauss syndrome. All received the "standard" treatment based on prednisone (1 mg/kg/day for 1 month and then slowly tapered) and cyclophosphamide (2 mg/kg/day for 6 months in severe cases). In nine patients, synchronised cycles with plasmapheresis and intravenous immunoglobulin (2 g/kg) were repeated monthly for 6 months and every other month for a further three cycles. Clinical (disease activity monitored by Birmingham vasculitis activity score (BVAS) and damage index (modified Rankin score)) and functional (C reactive protein, blood eosinophil count, and electromyogram-electoneurogram) parameters were collected during treatment and the 3 year follow up period. Results: After 12 months, all patients in the treatment group and four (44%) in the control group were in remission. At the end of the 3 year follow up period, we documented significant differences in BVAS (p<0.01), global damage (p<0.02), modified Rankin score (p<0.04), and the daily maintenance prednisone dose (p<0.002) between the two groups. We found a tendency towards lower frequency of relapse and incidence of osteoporosis in the treatment group. Conclusion: Complete clinical and functional recovery with a long term stable remission and a low incidence of side effects can be achieved by intravenous immunoglobulin associated with plasmapheresis in patients with Churg-Strauss syndrome.